Earthquake resistant design of underground structures and pipes - Kraus, Dieter (Vietnam Journal of Mechanics, 1995)
Underground Structures and Pipes can be analyzed as slender structures completely embedded in the soil. For the dynamical analysis soil and structure can be investigated by decoupled structural models. The horizontal layer system of the soil is modeled as a shear beam while for the structure a flexural beam is used. Both models will be finally coupled by elastic foundation.